2014
DOI: 10.1002/jhet.1796
|View full text |Cite
|
Sign up to set email alerts
|

A “One Pot,” Environmentally Friendly, Multicomponent Synthesis of 2‐Amino‐5‐cyano‐4‐[(2‐aryl)‐1H‐indol‐3‐yl]‐6‐hydroxypyrimidines and Their Antimicrobial Activity

Abstract: A series of multifunctional 2‐amino‐5‐cyano‐4‐[(2‐aryl)‐1H‐indol‐3‐yl]‐6‐hydroxypyrimidines (4a, 4b, 4c, 4d, 4e, 4f) was synthesized by multicomponent reaction of 3‐formylindole (1), cyanoethylacetate (2), and guanidine hydrochloride (3) with NaOH by using green chemical techniques, viz. microwave irradiation and grindstone technology. The same reactants when refluxed in ethanol also gave titled compounds (4a, 4b, 4c, 4d, 4e, 4f). Compared with conventional procedure, the reaction can be carried out under mild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
(21 reference statements)
0
7
0
Order By: Relevance
“…Inspired by recent reports on bio-orthogonal chemistry exploiting weakly or nonfluorescent reagents to produce highly fluorescent molecules, which could be exploited for tagging of biomolecules in living systems, especially in aqueous medium, and in continuation to our previous work on fluorescent coumarin-based compounds, herein, we describe a green protocol for the preparation of heterobioconjugate-based 1,4-disubsituted 1,2,3-traizoles through a 1,3-dipolar cycloaddition reaction using NaCl as a salting-out agent in water under ultrasonic irradiation at ambient temperature. Additional advantage of this protocol is recycling of the traditional Cu­(I) catalytic system up to seven cycles, which enhances the viability of this method by reducing the loading of toxic Cu.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by recent reports on bio-orthogonal chemistry exploiting weakly or nonfluorescent reagents to produce highly fluorescent molecules, which could be exploited for tagging of biomolecules in living systems, especially in aqueous medium, and in continuation to our previous work on fluorescent coumarin-based compounds, herein, we describe a green protocol for the preparation of heterobioconjugate-based 1,4-disubsituted 1,2,3-traizoles through a 1,3-dipolar cycloaddition reaction using NaCl as a salting-out agent in water under ultrasonic irradiation at ambient temperature. Additional advantage of this protocol is recycling of the traditional Cu­(I) catalytic system up to seven cycles, which enhances the viability of this method by reducing the loading of toxic Cu.…”
Section: Introductionmentioning
confidence: 99%
“…A one-pot three-component reaction of indole-3-aldehyde derivatives 1, ethyl cyanoacetate 6, and guanidine hydrochloride 69 under three different conditions, including microwave irradiation, grindstone technology and reux, was developed to afford 2-amino-5-cyano-4-[(2-aryl)-1H-indol-3-yl]-6-hydroxypyrimidines 70 (Scheme 26) 86 The products 70 were evaluated for their antimicrobial activity against nine pathogenic bacteria and showed mild to moderate activity.…”
mentioning
confidence: 99%
“…The IR spectrum of 9a-9v displayed absorption bands between 3371.5 and 3089.9 cm À1 corresponding to N-H, 1639.4-1423.4 cm À1 corresponding to C¼C and C¼N function. The 1 H-NMR spectrum of 9b in DMSO-d 6 displayed a triplet at δ 1.41 ppm and a multiplet at δ 3.23-3.25 ppm that corresponds to S-CH 2 CH 3 functionality, a singlet at δ 2.43 ppm integrating for three protons was assigned to methyl protons of pyrimidine-CH 3 . A singlet that appeared at δ 8.06 ppm was observed because of the protons of NH 2 group.…”
Section: Resultsmentioning
confidence: 99%
“…Pyrimidine ring system is very important because several of its derivatives have been found to be medicinally useful. Synthetic studies of fused pyrimidines have been reported extensively because of their structural diversity, associated with a wide spectrum of biological activity including insecticidal , acaricidal , fungicidal , antimicrobial , herbicidal , antiviral , and anticanceral activity . In the ambit of application in antiviral area, many pyrimidine derivatives with good anti‐tobacco mosaic virus (TMV) activity have been described.…”
Section: Introductionmentioning
confidence: 99%